Program Perawatan Komunikasi Satelit (VSAT) Di Desa Tumpak Lombok Tengah - Made Sutha Yadnya; Sultan Sultan; Agung Budi Muljono; Paniran Paniran; SMA Sasongko; I Made Ari Nrartha (Universitas Mataram, 2023)
Satellite communications, especially VSAT in Tumpak Village, are often disrupted, so the Electrical Engineering Department team at the University of Mataram did community service. A maintenance program was carried out to maintain the continuity of satellite communications, especially VSAT, which was carried out with moderate results because the equipment has been used for more than 5 years. The provider has changed and the available bandwidth is still small, it needs to increase the speed, but the finances are also big for the village, they have to have a reserve fund